REPRESENTATION, INCLUSION AND SOCIAL JUSTICE IN WORLD LANGUAGE TEACHING - Padilla, Lillie; Vana, Rosti ([S.l.] : ROUTLEDGE, 2024)
This volume introduces teaching methodologies for improving and incorporating representation, inclusion and social justice perspectives in the world language curriculum. Chapters present state-of-the-art research and cover many different language contexts, including French, Spanish, Mandarin, and Portuguese. Authors discuss difficult and hot topics, such as Critical Language Awareness, Critical Race Theory, non-binary language use in gendered languages, culturally sustaining curriculum, teaching heritage language speakers, and more. Ideal for graduate courses, students, and scholars in world language education, the volume offers new pathways and strategies for promoting diversity and equity in the classroom.
Keywords: Language and languages -- Study and teaching; Multicultural education; FOREIGN LANGUAGE STUDY / General